2009
DOI: 10.1093/eurheartj/ehp171
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life assessment after percutaneous aortic valve implantation

Abstract: Our preliminary results show a marked short-term improvement in functional status and physical and mental health in patients underwent PAVI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(42 citation statements)
references
References 19 publications
3
38
0
1
Order By: Relevance
“…21,22 Quality of life is an important clinical outcome measure and is 1 of the main reasons that TAVI is conducted. 23 As such, anything negatively affecting HRQoL, such by guest on May 11, 2018 http://circinterventions.ahajournals.org/ Downloaded from as silent cerebral emboli, would be of concern. This study has shown that for both TAVI and SAVR new cerebral emboli did not detrimentally affect patient-reported HRQoL at 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Quality of life is an important clinical outcome measure and is 1 of the main reasons that TAVI is conducted. 23 As such, anything negatively affecting HRQoL, such by guest on May 11, 2018 http://circinterventions.ahajournals.org/ Downloaded from as silent cerebral emboli, would be of concern. This study has shown that for both TAVI and SAVR new cerebral emboli did not detrimentally affect patient-reported HRQoL at 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…The CoreValve prosthesis improves hemodynamic aortic valve function and results in an improvement in both quality of life and mortality. 8,27,28 The study patients received the CoreValve device, first used in a human by Grube et al 29 in 2005. It consists of a bioprosthetic valve (derived from porcine pericardium) mounted and sutured within a laser-cut nitinol frame.…”
Section: Discussionmentioning
confidence: 99%
“…12). The encouraging mid-and long-term results of this technique, together with increased patient comfort, shortened intensive care and hospital stay, and the avoidance of cardiopulmonary bypass, make this non-surgical technique extremely appealing (Ussia et al, 2009). …”
Section: Transcatheter Aortic Valve Implantationmentioning
confidence: 99%
“…Device sizing and positioning are the main challenges, but vascular complications, electrical conduction abnormalities and post-procedural aortic regurgitation still remain major safety concerns. In addition, according to the current position statement, TAVI is indicated only in patients with severe symptomatic aortic stenosis, and who are considered at high or prohibitive risk for conventional surgery (Ussia et al, 2009.…”
Section: Transcatheter Aortic Valve Implantationmentioning
confidence: 99%